2013
DOI: 10.3174/ajnr.a3561
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Coil Mass Artifacts in High-Resolution Flat Detector Conebeam CT of Cerebral Stent-Assisted Coiling

Abstract: Background and purpose Developments in flat-panel angiographic c-arm systems have enabled visualization of both the neurovascular stents and host arteries in great detail, providing complementary spatial information in addition to conventional DSA. However, the visibility of these structures may be impeded by artifacts generated by adjacent radio-attenuating objects. We report on the use of a metal artifact reduction (MAR) algorithm for high resolution contrast-enhanced CBCT (VasoCT) for follow-up imaging of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…The first FDCT-adequate MAR algorithm proposed by Prell et al 2 used a nonlinear interpolation procedure to restore corrupted data and has subsequently been shown to decrease metal artifacts of FDCT images obtained for neuroendovascular procedures. 13,14 This finding correlates with the results of the current study in which we show that the MAR algorithm described above significantly lowered the amount of metal artifacts hindering visualization of the intracranial tissues. Another strategy used to successfully reduce metal artifacts in FDCT imaging is to subtract a volume reconstructed from data corrupted by artifacts from an initial uncorrected volume reconstruction without a nonlinear interpolation process to replace the corrupted data.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The first FDCT-adequate MAR algorithm proposed by Prell et al 2 used a nonlinear interpolation procedure to restore corrupted data and has subsequently been shown to decrease metal artifacts of FDCT images obtained for neuroendovascular procedures. 13,14 This finding correlates with the results of the current study in which we show that the MAR algorithm described above significantly lowered the amount of metal artifacts hindering visualization of the intracranial tissues. Another strategy used to successfully reduce metal artifacts in FDCT imaging is to subtract a volume reconstructed from data corrupted by artifacts from an initial uncorrected volume reconstruction without a nonlinear interpolation process to replace the corrupted data.…”
Section: Discussionsupporting
confidence: 89%
“…An effective means of reducing the metal artifacts caused by metal implants would make FDCT imaging an ideal postprocedural technique to visualize complications such as intracranial hemorrhage, residual filling of aneurysms, or thrombus within newly deployed stents. Several strategies have been proposed to reduce the metal artifacts for conventional multidetector row CT, 13 but these strate-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, based on their own versions of a MAR algorithm, have further demonstrated the visualization usefulness of the stent strut and parent vessels in stent-assisted coiling. 9,10 However, the efficacy of the MAR algorithm, as described above in managing different metal objects, has not been reported, to our knowledge. The patients in our study did not undergo FDCT before the operation.…”
Section: Discussionmentioning
confidence: 94%
“…Further studies based on a previous MAR algorithm 8 have demonstrated the success in coiling and stentassisted coiling FDCT and CT angiography. 9,10 However, the comparison of the efficacy of artifact reduction for various sizes and types of metal objects was seldom discussed. In this study, we investigated whether a MAR prototype software could reduce artifacts stemming from different high-attenuation implants and improve the diagnostic confidence of radiologists.…”
mentioning
confidence: 99%